Satu Bulan Penerapan Yoga Anak Meningkatkan Konsentrasi Belajar Usia Prasekolah - Ida Sofiyanti; Heni Setyowati (Indonesian Journal of Midwifery (IJM), 2021)
Based on Riskesdas 2018, 29.9% of Infants Under Two Years (Baduta) experienced very short and short nutrition. Still based on the results of the 2018 Riskesdas, there is a comparison of child development in children aged 36-59 months in Indonesia with a total development index of 88.3%, of which 64.6% is literate, 97.8% is physical, 69.9% is social-emotional, and 95. 2% learning. The ability and development of children need to be stimulated so that children can grow and develop optimally and according to their age. Stimulation is stimulation (sight, speech, hearing, touch) that comes from the child's environment. Children who get directed stimulation will develop faster than children who do not even get stimulation. Various efforts have been made to provide stimulation to children, one of which is by using Yoga activities. This study aims to determine the effect of yoga on children on learning concentration of preschool age children. The population and sample in this study were students in class A and class B with a total of 30 students, 15 students for the experimental group, and 15 students for the control group. This study uses a quasi-experimental research (Quasi Experimental) design used Non Equevalent Control Grub Design. The parametric hypothesis test used is the dependent t-test because the data is normally distributed. The test results stated that there were differences in the level of concentration in learning after being given yoga treatment for children for one monthAbstrak Berdasarkan Riskesdas 2018, 29,9 % Bayi Bawah Dua Tahun (Baduta) mengalami gizi sangat pendek dan pendek. Masih berdasarkan hasil Riskesdas 2018 didapatkan perbandingan perkembangan anak pada anak usia 36-59 bulan di Indonesia dengan total indeks perkembangan 88,3 %, dimana 64,6 % literasi, 97,8 % fisik, 69,9 % social emosional, dan 95,2 % learning. Kemampuan dan tumbuh kembang anak perlu diberikan stimulasi agar anak dapat tumbuh dan berkembang secara optimal dan sesuai umurnya. Stimulasi adalah perangsangan (penglihatan, bicara, pendengaran, perabaan) yang datang dari lingkungan anak. Anak yang mendapat stimulasi yang terarah akan lebih cepat berkembang dibandingkan anak yang kurang bahkan tidak mendapat stimulasi. Berbagai upaya yang dilakukan untuk memberikan stimulasi kepada anak salah satunya dengan mengunakan kegiatan Yoga. Penelitian ini bertujuan mengetahui pengaruh yoga pada anak terhadap konsentrasi belajar anak usia Prasekolah. Populasi dan Sampel dalam penelitian ini adalah Siswa kelas A dan Kelas B sejumlah 30 siswa dimana 15 siswa untuk kelompok eksperimen, dan 15 siswa untuk kelompok kontrol. Penelitian ini menggunakan penelitian eksperimen semu (Quasi Experimental) desain yang digunakan Non Equevalent Control Grub Design. Uji hipotesis parametrik yang digunakan adalah uji dependent t-test karena data berdistribusi normal. Hasil uji menyatakan ada perbedaan tingkat konsentrasi belajar setelah diberikan perlakuan yoga anak selama satu bulan.Â